COVID-19 pandemic or chaos time management: first-line worker shortage – a qualitative study in three Canadian Provinces - Beogo, Idrissa; Bationo, Nebila J.; Sia, Drissa; Collin, Stephanie; Kinkumba Ramazani, Babou; Létourneau, Aurée-Anne; Ramdé, Jean; Gagnon, Marie-Pierre; Tchouaket, Eric N. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Over the successive waves of the COVID-19 pandemic, front-line care workers (FLCWs) —in this case, at long-term care facilities (LTCFs)— have been the backbone of the fight. The COVID-19 pandemic has disproportionately affected LTCFs in terms of the number of cases, deaths, and other morbidities, requiring managers to make rapid and profound shifts. The purpose of this study is to describe the effects of the pandemic on LTCF services offered and LTCFs staff dedicated to linguistic minorities in three Canadian provinces. Methods This qualitative descriptive study involved eleven managers and fourteen FLCWs, from six LTCFs of three Canadian provinces (New-Brunswick, Manitoba and Quebec). A qualitative content analysis was performed to identify key themes describing the effects of the COVID-19 pandemic on the services offered and the management of LTCFs staff. Results Based on participants’ experiences, we identified three main categories of themes. These macro-themes are as follows: (i) organization and management of staff, (ii) communication and decision-making method, and (iii) staff support. Conclusion The study highlighted the tremendous impact of COVID-19 on direct care staff in terms of the high risks associated with caring for LTCFs residents, which are exacerbated by absences and resignations (sometimes up to 50% of staff), resulting in higher resident to FLCWs ratios. Team members had to support each other, they also received accolades and appreciation from the residents.. Finally, the pandemic led to the rethinking of management procedures centred on a coordinated, inclusive and more hands-on management approach.